Evolution of the dry-wet variations since 1834 CE in the Lüliang Mountains, north China and its relationship with the Asian summer monsoon. (February 2021) - Cai, Qiufang; Liu, Yu; Zhang, Hanyu; Song, Huiming; Li, Qiang; Sun, Changfeng; Wang, Lu; Fang, Congxi; Liu, Ruoshi
Highlights: Spring-early summer droughts threaten crops and vegetation in North China. February-June SPEI was reconstructed since 1834 CE by multi-species tree rings. Reconstruction captures the catastrophic droughts in the 1920 s and 1876–1878 CE. There are spatiotemporal differences in dry/wet variations in northern China. Dry/wet variation in North China is influenced by the Asian summer monsoon system. Abstract: Under the background of global climate change, arid to semi-humid areas are more vulnerable to extreme climate, such as floods and droughts. To better predict and cope with future climate change, more local and regional long-term high-resolution climate reconstructions, hydroclimate in particular, are required. Based on a 174-year regional tree-ring-width chronology, we reconstructed the February–June Standardized Precipitation Evapotranspiration Index (SPEI26 ) history in the Lüliang Mountains, North China (NC). Reconstructed SPEI26 is expected to reflect the dry-wet variation from spring to early summer (STES) of NC with an explained variance of 43.8% for the instrumental record (1951–2007 CE). The reconstruction reveals three comparatively dry (1857–1878, 1919–1929 and 1995–2001 CE) and four comparatively wet (1883–1895, 1934–1944, 1952–1961 and 1980–1984 CE) periods during 1834–2007 CE. Although a drying trend is seen since the 1950s, an advent of wetting since the end of the 1990s is expected. As the driest period in the reconstruction, 1919–1929 CE records the widespread catastrophic 1920s drought in northern China. In addition to the local hydroclimatic signal, the reconstruction also reflects hydroclimatic variation over a large portion of northern China, which is evidented by the comparison with other hydroclimatic records and regional dry-wet index. Strength of the Indian summer monsoon and the East Asian summer monsoon in the previous year play vital roles in the STES dry-wet variations. Moreover, Atlantic Multi-decadal Oscillation index influencs the hydroclimate in NC by influencing the Asian summer monsoon system.